Grammar production rules as a formalism to specify user interface - Albertas Čaplinskas (Lietuvos Matematikos Rinkinys)
Event-driven automaton is an vvide-accepted formalism used to specify abstract user interface. However, this formalism has some disadvantages. For example, if a data base is used, it is difficult to distinguish what events occur in current and what in previous computations. Grammar production rules as a formalism to specify abstract user interface are proposed in this paper. Some advantages of this formalism are demonstrated.